AGE AND PREGNANCY DISTANCE AS A RISK FACTOR FOR ANEMIA CAUSES IN PREGNANT MOTHERS IN THE AREA OF PUBLIC HEALTH CENTRE OF BANJARNEGARA REGENCY - Dewie Sulistyorini; Ratih Subekti (Siklus : Journal Research Midwifery Politeknik Tegal, 2020)
Anemia is a condition where the body has a few numbers of red blood cells (erythrocytes). This condition is commonly found in pregnant women. WHO determines the incidence of anemia in pregnancy ranging from 20% to 89% by determining Hb less than 11 gr%. The purpose of this study was to determine the age and distance of pregnancy in pregnant women with anemia in the public health centre in Banjarnegara. The method used in this study was descriptive analysis. Sampling-based on total sampling, amounting to 29 people. The results showed that most of the "low-risk age group" numbered 25 respondents (86%), and the majority of respondents "low-risk pregnancy distance" totalled 27 respondents (93%). In conclusion, most respondents in the age and distance of pregnancy were low-risk categories. However, it was better for a woman who plans to become pregnant to pay attention to proportional age to get pregnant, and a healthy pregnancy distance, one of the things that can be done is to use contraception that is appropriate to the conditions the woman and her purpose whether to deploy, thin out or stop the pregnancy. Keywords: Age, pregnancy distance, anemia, pregnant women